THE NEXUS OF SECURITY AND INTEREST: MALAYSIA'S APPROACH TO ARAB-ISRAELI NORMALIZATION - Ainul Asyraf Lokman; Mohd Roslan Mohd Nor, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The Arab-Israeli normalization, characterized by the Abraham Accords and subsequent diplomatic engagements, has sparked significant debate among regional actors especially among Muslim countries. In this context, Malaysia's response is analyzed by employing a combined theoretical framework of Regional Security Complex (RSC) theory and national interest theory. The study employs a qualitative method of analysis of official statements, policy documents, and diplomatic engagements. It also examines the historical context of Malaysia's stance on the Israeli-Palestinian conflict and the shifts and nuances of its response in light of recent events. In addition, this study examines the domestic factors, such as public opinion, political dynamics, and the influence of religious and civil society actors, that influence Malaysia's foreign policy decisions. This study reveals that Malaysia has voiced its opposition to the process of normalisation, which has been influenced by regional security concerns rooted in Muslim solidarity and the support for Palestinian rights. Additionally, Malaysia's opposition is driven by its own national interests, encompassing domestic politics and economic relations with Arab nations.